Changing for Good - Diclemente Carlo C; Norcross, John C.; Prochaska James O (Harper & Brothers, Publishers, 2006)
This book offers simple self-assessments, informative case histories, and concrete examples to help clarify each stage and process. Introduction: A Scientific Revolution, The Science, How You Change, When You Change, Making Changes, The Applications, Precontemplation - Resisting Change, Contemplation - Change on the Horizon, Preparation - Getting Ready, Action - Time to Move, Maintenance - Staying There, Recycling - Learning from Relapse, A Changer's Manual, Termination - Exiting the Cycle of Change, Appendices, Foolish Freedom, A New Paradigm, Bibliography, Index.